2013
DOI: 10.1590/s1984-29612013000400022
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania infection in a population of dogs: an epidemiological investigation relating to visceral leishmaniasis control

Abstract: Identification of factors associated with Leishmania infection in dogs is essential for targeting visceral leishmaniasis control actions. Thus, the present study analyzed some of these factors in a population of dogs in a Brazilian municipality, along with the limitations of control strategies implemented there. The association between the exposure variables and occurrences of infection was analyzed through logistic regression models. The disease control interventions were treated qualitatively. Out of the 755… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
6
1
3
Order By: Relevance
“…Governador Valadares city is a re-emergent focus of visceral leishmaniasis with a high number of human cases due to L. (L.) infantum and a high prevalence of infected dogs36. To our knowledge, this article presents the first report of L. (L.) amazonensis in Governador Valadares and shows a potential risk for current control efforts in the area that have been designed considering only the presence of L. (L.) infantum .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Governador Valadares city is a re-emergent focus of visceral leishmaniasis with a high number of human cases due to L. (L.) infantum and a high prevalence of infected dogs36. To our knowledge, this article presents the first report of L. (L.) amazonensis in Governador Valadares and shows a potential risk for current control efforts in the area that have been designed considering only the presence of L. (L.) infantum .…”
Section: Discussionmentioning
confidence: 91%
“…As part of a study aiming at characterizing Leishmania isolates circulating in the city of Governador Valadares, Minas Gerais state, Brazil, we have sequenced the genomes of several Leishmania isolates from this focus. Genome sequencing of five isolates obtained from dogs revealed the presence of L. (L.) amazonensis in this endemic region of tegumentary and visceral leishmaniasis36. The genomic analysis performed in this study of the two L. (L.) amazonensis isolates allowed us to explore some unique features in terms of chromosome and gene copy number variations that are unique to this species.…”
Section: Discussionmentioning
confidence: 91%
“…Coura-Vital et al [ 34 ] found no association between SIZE and CanL, coinciding with the results of this study. On the other hand, Penaforte et al [ 35 ] found such an association and suggested that large dogs would be subjected to infected sand fly bites because they are used as guard dogs. A higher seroprevalence of CanL was found in large dogs than in small and medium dogs, but SIZE lost importance when controlled by the other variables, especially WHERE.…”
Section: Discussionmentioning
confidence: 99%
“…Dogs not adopted were returned to the streets after the lactation period. Additional activities recommended by the Brazilian program on visceral leishmaniasis control, such as the culling of Leishmania -infected dogs, were also carried out on a regular basis [ 31 , 32 ], as well as vaccination campaigns against rabies [ 33 ].…”
Section: Methodsmentioning
confidence: 99%